2001
DOI: 10.1002/1615-4169(20010226)343:2<201::aid-adsc201>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

ROTACAT: A Rotating Device Containing a Designed Catalyst for Highly Selective Hydroformylation

Abstract: A novel concept is presented for the immobilization of a homogeneous catalyst. A hydroformylation catalyst was covalently anchored to monoliths that were constructed as the blades of a mechanical stirrer and used in a batch process. The catalyst was effective in the hydroformylation of both higher and lower alkenes and showed a high regioselectivity for the linear aldehyde. The concept was proven to be useful in a liquid organic and aqueous phase as well as in the gas phase and the catalyst could be used numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…For example, Moulijn et al reported a monolith stirrer covered with a manganese oxide catalyst to decompose hydrogen peroxide. Sandee et al constructed a mechanical stirrer with hydroformylation catalyst-anchored monoliths as the blades, which shows effectiveness in the hydroformylation of both higher and lower alkenes. Our group has also developed a series of integrated catalytic agitators with a specific structure and catalytic species, including Fe-AI, , Ag-AI, and Pd-AI, which exhibit high catalytic activity for 4-NP reduction, Fenton reaction, Suzuki coupling reaction, etc., and feature great separation and recycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Moulijn et al reported a monolith stirrer covered with a manganese oxide catalyst to decompose hydrogen peroxide. Sandee et al constructed a mechanical stirrer with hydroformylation catalyst-anchored monoliths as the blades, which shows effectiveness in the hydroformylation of both higher and lower alkenes. Our group has also developed a series of integrated catalytic agitators with a specific structure and catalytic species, including Fe-AI, , Ag-AI, and Pd-AI, which exhibit high catalytic activity for 4-NP reduction, Fenton reaction, Suzuki coupling reaction, etc., and feature great separation and recycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…Monoliths are also considered attractive catalyst support alternatives compared to conventional carriers in other heterogeneous catalysis applications, including liquid-phase catalysis. [23][24][25][26] Monoliths feature a high void fraction and large geometric surface area, which results in a large contact area between the catalyst and reactants and low-pressure drop under flow conditions. 24 The most widely used monolith support material is based on cordierite (2MgO .…”
Section: Resultsmentioning
confidence: 99%
“…Monolithic structures are widely used in off-gas treatment, e.g., automotive exhaust gas purification and de-NOx of power plant stack gases . Monoliths are also considered attractive catalyst support alternatives compared to conventional carriers in other heterogeneous catalysis applications, including liquid-phase catalysis. Monoliths feature a high void fraction and large geometric surface area, which results in a large contact area between the catalyst and reactants and low-pressure drop under flow conditions . The most widely used monolith support material is based on cordierite (2MgO·2Al 2 O 3 ·5SiO 2 ), and it contains a macroporous wall structure. This macroporous space may create an obstacle for applying a thin uniform layer of the catalyst since it can lead to deposition of ineffective active phase within the macro-pores, where it is not accessible for substrates .…”
Section: Resultsmentioning
confidence: 99%
“…The semibatch hydrogenation experiments were conducted in a monolithic stirrer reactor. This reactor type has been used for several studies and has great potential in the fine chemical industry. The conditions used were 2.3 bar, 600 rpm, and 24.4 ± 0.3 °C.…”
Section: Methodsmentioning
confidence: 99%